Cost-Effectiveness Analysis of Nefecon versus Best Supportive Care for People with Immunoglobulin A Nephropathy (IgAN) in the United States - Ramjee L; Vurgun N; Ngai C; Patel M; Tremblay G (Dove Medical Press, 2023)
Lauren Ramjee,1 Nesrin Vurgun,1 Christopher Ngai,2 Mit Patel,3 Gabriel Tremblay1 1Health Economics & Outcomes Research (HEOR), Cytel, Inc, Waltham, MA, USA; 2Market Access, Calliditas NA Enterprises, New York, NY, USA; 3Health Economics & Outcomes Research (HEOR), Calliditas NA Enterprises, New York, NY, USACorrespondence: Gabriel Tremblay, Cytel, Inc, 1050 Winter Street #2700, Waltham, MA, 02451, USA, Tel +1 581-980-3151, Email gabriel.tremblay@cytel.comPurpose: To estimate the cost-effectiveness of Nefecon in addition to the best supportive care (BSC) vs BSC in a hypothetical cohort of commercially insured adult patients with primary immunoglobulin A nephropathy (IgAN) from a United States (US) societal perspective.Methods: A lifetime horizon, semi-Markov model was developed that consisted of nine health states: chronic kidney disease (CKD) stage 1, 2, 3a, 3b, 4, end-stage renal disease (ESRD) with dialysis, ESRD without dialysis, post-kidney transplant, and death. Health state occupancy was estimated from individual patient-level data from the Phase 3 randomized controlled trial NefIgArd Part A (NCT03643965). Additional scenarios evaluated the impact of varying the time horizon, discounting, costs included, rounds of treatment, and the method used to calculate transition probabilities.Results: In the deterministic base case analysis over a lifetime horizon, Nefecon plus BSC (hereafter Nefecon) had an incremental cost of $3,810 vs BSC. Nefecon resulted in a mean survival gain of 0.247 quality-adjusted life years (QALYs), 0.195 life years (LYs), and 0.244 equal value life years (evLYs) vs BSC alone - this resulted in incremental cost-effectiveness ratios (ICERs) of $15,428 per QALY, $19,502 per LY, and $15,611 per evLY gained. Probabilistic sensitivity analyses estimated that with willingness to pay thresholds of $100,000, $150,000, and $250,000 per QALY gained, Nefecon would be cost-effective over BSC in 66.70%, 75.02%, and 86.82% of cases, respectively. In the scenario analysis, Nefecon remained cost-effective with 4 rounds of treatment.Conclusion: Nefecon was associated with LY and QALY gains vs BSC, with an incremental cost of $3,810. Based on these values, with a willingness to pay threshold of $100,000 per QALY gained, Nefecon was found to be a cost-effective treatment for US adults with primary IgAN.Keywords: primary glomerulonephritis, glomerular disease, end-stage kidney disease, ESRD, TARPEYO®, targeted-release budesonide, Nefecon